Developing Islamic Education and Local Culture Textbooks - Baderiah Baderiah; Ahmad Munawir; Firman Firman (STAI Hubbulwathan Duri, 2022)
This study aimed to determine the need for Islamic education courses and local culture at the Faculty of Tarbiyah and Teacher Training IAIN Palopo and to determine the prototype, validity, practicality, and effectiveness of teaching materials for Islamic education and local culture based on the integrative-interconnective paradigm at the Faculty of Tarbiyah and Teacher Training IAIN Palopo. The type of research used was development research. The research was conducted at the Palopo State Islamic Institute in the 2020/2021 academic year. This study concludes that a textbook that can integrate Islamic education and local culture is needed, consisting of 7 chapters, 28 subchapters, and 28 materials; textbooks are very valid, practical, and effective to be used as teaching materials for Islamic education courses local culture.